Activist manipulation dynamics - Esat Doruk Cetemen; Gonzalo Cisternas; Aaron Kolb; S. Viswanathan (Federal Reserve Bank of New York, 2022)
Two activists with correlated private positions in a firm's stock, trade sequentially before simultaneously exerting effort that determines the firm's value. We document the existence of a novel linear equilibrium in which an activist's trades have positive sensitivity to her block size, but such orders are not zero on average: the leader activist manipulates the price to induce the follower to acquire a larger position and thus add more value. We examine the implications of this equilibrium for market outcomes and discuss its connection with the prominent phenomenon of "wolf-pack" activism-multiple hedge funds engaging in parallel with a target firm. We also explore the possibility of other equilibria where the activists trade against their initial positions.
Keywords: D82; G14; G23; 330; activism; insider trading; noisy signaling; price manipulation; hedge funds